Analysis of students problem solving ability by using polya steps in linear program material - NH Sari; S Sutiarso; S Dahlan (Pascasarjana Universitas Pendidikan Indonesia, 2020)
The purpose of this study is to analyze students problem solving ability by using polya steps in linear program material. This was a descriptive study that used a qualitative approach with 103 students of XI grade of science at SMA Negeri 1 Kota Bumi as the subject of the study. The data was collected through the technique of a written test, which consisted of two questions. The result of the research showed that the ability of problem solving in students of XI grade of science at SMA Negeri 1 Kota Bumi were good, which were 17 students or 16,50% was very good at problem solving, 53 students or 51,47% was good enough at problem solving, 28 students or 27,18% was less good at problem solving, and 5 students or 4,85% was goodless at problem solving. The results of each indicator of problem solving ability was the indicator of understanding the problem was 87,86%, indicator of arranging a plan was 45,99%, indicator of carrying out a plan was 39,31%, and indicator of re-check was 34,91%.